Gold nanoparticle printed coverslips to facilitate fluorescence-TEM correlative microscopy. - Neeraj Prabhakar; Anni Määttänen; Jouko Peltonen; Pekka Hänninen; Markus Peurla; Jessica M Rosenholm (My University, 2022)
Correlative light and electron microscopy (CLEM) allows combining the advantages of fluorescence microscopy and electron microscopy for cell imaging. Rare phenomenon expressing cells can be studied by specifically tagged fluorophores with fluorescence microscopy. Subsequently, cells can be fixed and ultra-structural details can be studied with transmission electron microscopy (TEM) at a higher resolution. However, precise landmarks are necessary to track the same cell throughout the CLEM process. In this technical report, we present a high contrast inkjet-printed gold nanoparticle patterns over commercial glass coverslip to facilitate cell tracking with correlative microscopy. High contrast and strong reflection from nano gold pattern can be used as a fixed landmark for cell identification with fluorescence microscopy. Nano gold printed letters over coverslips are visible in resin blocks, which can be further used to identify the cell of interest for performing sectioning of embedded cell blocks for TEM.